Determinan Produktivitas Kerja Karyawan di SMP Nasional Denpasar - Tambun, I Nengah; Suidarma, I Made (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of the work environment, work discipline, and work motivation on employee productivity at SMP Nasional Denpasar. The background of the study stems from the high level of employee absenteeism in 2024, which reflects weak human resource management. This condition not only disrupts organizational work stability but also directly impacts employee productivity, thus requiring an empirical study to identify the determining factors. The research approach uses a quantitative method with 49 respondents determined through saturated sampling. Data collection was carried out through observation and questionnaires with a Likert scale, and analyzed us-ing multiple linear regression with validity, reliability, and classical assumption tests. The results show that all three variables contribute to employee productivity. These find-ings provide empirical evidence for the development of human resource management in educational institutions.